Impact of Otitis Media on Speech and Language in Children - Muhammad Ahmed, Saira Zaman, Athar Adnan Uppal, Nasir Riaz, Aneela Sattar, Anees-Ur-Rehman, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Otitis media, a prevalent middle ear infection in children, has been associated with speech and language development deficits. Recurring or chronic episodes can lead to fluctuating conductive hearing loss, potentially impacting phonological processing, vocabulary acquisition, and speech intelligibility. Understanding these effects is crucial for early intervention and management. Objective: To investigate the impact of recurrent or chronic otitis media on phonological processing, vocabulary development, syntactic abilities, and overall speech intelligibility in children. Methodology: This descriptive study was conducted at Department of Rehabilitation Sciences, The University of Lahore from 1st July 2023 to 31st October 2023. A total of 120 children participated, comprising 60 diagnosed with recurrent or chronic otitis media and 60 age-matched controls without otitis media. Audiological and language assessments included otoscopic examinations, tympanometry, pure tone audiometry, the Preschool Language Scale (PLS-5), and the Goldman-Fristoe Test of Articulation (GFTA-3). Data were analyzed using SPSS version 26.0 to determine correlations between hearing thresholds and language performance. Results: Children with recurrent otitis media exhibited significantly lower expressive and receptive language scores, reduced phonological awareness, and impaired speech perception compared to the control group (p < 0.05). Conductive hearing loss due to otitis media was linked to articulation errors and diminished speech intelligibility. Additionally, delays in pragmatic language skills were observed, affecting social communication. Conclusion: Chronic otitis media negatively affects speech and language development, emphasizing the need for early audiological assessments and multidisciplinary interventions. Medical management combined with speech therapy can mitigate some of the language deficits associated with otitis media. Keywords: Otitis media, speech and language development, conductive hearing loss, phonological processing, articulation errors, pragmatic language skills, early intervention